A Compendium of the Wondrous Deeds of Caterina da Racconigi: Hagiography or Philosophical Treatise? - Zarri, Gabriella (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2019)
Gianfrancesco Pico’s interest in Caterina da Racconigi, a mystic and prophet revered in Piedmont in the first decades of the sixteenth century, was born out of a scientific curiosity prior to becoming devout admiration. The Compendio delle cose mirabili, Gianfrancesco’s last work, written after the completion of his Life of Savonarola, is a continuation of his treatises on prophecy and premonition and on the discernment of spirits and witchcraft; it aims to observe and describe the mystical phenomena attributed to a woman whose conduct is inspired by a specific model of holiness. The Compendio is therefore a composite text, part scientific treatise and part hagiography. This article examines the text in terms of hagiography by relating it to the model of Catherine of Siena and to the lives of the living saints that inspired Caterina da Racconigi’s own behaviour. It also explores the significance of the work within Gianfrancesco’s religious thought.